EMPOWERMENT OF WOMEN FARMER GROUPS IN THE USE OF HOUSEHOLD WASTE AS FERTILIZER IN VEGETABLE CULTIVATION: KEBERDAYAAN KELOMPOK WANITA TANI (KWT) DALAM PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI PUPUK PADA BUDIDAYA SAYURAN - Firda Khoirotunnisa Elhikmah; Rudi Hartono; Nazaruddin (Jurnal Penyuluhan Pertanian, 2022)
The state of the population will be related to the state of household waste generated in daily activities. Household waste management by women farmer groups in Maja sub-district in general has not been carried out properly. Women who are members of women’s farmer groups in Maja subdistric 0.72%. This study aims to describe the level of empowerment of women's farmer groups, analyze the factors that influence the empowerment of women's farmer groups, and formulate a strategy to increase the empowerment of women's farmer groups in the use of household waste into fertilizer, assessing its impact of fertilizer application. Respondents in this study amounted to 58 people, namely members of women's farmer groups in Pageraji Village, Wanahayu Village, and Tegal Sari Village with saturated sampling method. The data analysis used in this research is descriptive analysis and multiple linear regression analysis. The results showed that the empowerment of women's farmer groups was in the moderate category with a willingness indicator of 60%, and an indicator of ability 55%. The factors that influence the empowerment of women's farmer groups are extension activities and the function of women's farmer groups. The strategy is carried out with outreach activities to women farmer groups by determining the material based on descriptive analysis.